The socio-religious impact of facebook on muslim youths in Epe, Lagos state, Nigeria (2018)
Facebook is the most frequently used social Media platform the world over. The platform is known for keeping in-touch with family members and friends irrespective of the distance. The medium is also utilised in the dissemination of information. One of the uses of Facebook is proselytfation and the dissemination of socio-religious information. Studies have been earned out on the educational and social aspects of Facebook with little attention on its socio-religious impact in Nigeria. The study, therefore, investigates the socioreligious use of Facebook and the impact of such on Muslims youths in Epe, Lagos State, Nigeria. One hundred copies of a questionnaire were randomly administered on Muslim youths in Epe, Lagos State and interviews were conducted with some Muslim youth leaders in the area. From the findings, Facebook has served as a platform for sharing of information about Islamic programmes and the education of Muslim youths in the study area. It has also enhanced Islamic understanding among the youths. However, youths were discovered to be addicted to Facebook, thereby spending time that could have been utilised on devotional activities on the plaform. Facebook has had considerable impact on the Muslim youths in Epe, Lagos State. Parents and Islamic organisations have the role to educate youths on the proper use of Facebook.